Performance and exergoeconomic assessment of of integrated organic rankine cycle with solar combined cycle system on sustainable power generation in Iraq - Abdulrazzak Akroot; Ayaa Faraj (Engineering and Technology Journal, 2025)
This study presents a comprehensive performance and exergoeconomic assessment of a solar-driven triple combined cycle (TCC) power system integrated with a rock bed thermal storage unit and an Organic Rankine Cycle (ORC) for enhanced sustainable power generation in Iraq. The proposed system combines Brayton, Rankine, and Organic Rankine Cycle (ORC) cycles to maximize energy recovery from both high- and low-grade heat sources. The integration of the ORC unit significantly improves system efficiency by utilizing residual thermal energy that would otherwise be wasted. The analysis used Engineering Equation Solver (EES) software, incorporating monthly climatic data from Salahaddin, Iraq. Thermodynamic and exergoeconomic evaluations assessed energy efficiency, exergy destruction, component costs, and electricity production cost. Unlike previous studies, this research introduces an advanced exergoeconomic perspective, providing a more realistic assessment of technical and economic performance. Results indicate that the system achieves a power output of 12.4 MW in June, with energy and exergy efficiencies of 37.37% and 40.8%, respectively, and a unit electricity cost of $33.31 per hour. In January, the output increases to 14.17 MW with higher exergy efficiency (46.21%) but at a higher cost due to reduced solar availability. The addition of the ORC unit enhances both energy recovery and economic performance, especially during periods of low solar input, supporting the system’s viability for year-round renewable power generation.